MALAY SCHOOLS AND SCHOOL LIBRARIES IN THE STRAITS SETTLEMENTS UNDER BRITISH COLONIAL RULE BEFORE THE SECOND WORLD WAR, 1876-1941 - Lim, Peng Han (Malaysian Journal of Library and Information Science, 2008)
This article attempts to re-examine whether school libraries in the Straits Settlements were a post war innovation by going through primary and secondary historical records available. It was discovered that although the first policy to initiate school libraries in Malay schools was stated in 1899, it was unlikely to have taken off since the only press to publish Malay school books was discontinued the same year. It was not until 1925 that the Malay Translation Bureau was reorganized to produce Malay school books and reading books. However, not much books were translated and finalized as there was no more than nine staff employed in the Bureau when compared to 250 staff in Balai Pustaka in the Netherlands East Indies (NEI). By 1936, 165 out of 171 Malay boys’ schools had school libraries. However, the libraries were limited to having 30 titles each. In contrast school libraries in the NEI had 328 titles. Therefore not much efforts were put in to make the Malay Translation Bureau into a full-fledged publishing house, like Balai Pustaka, to meet a growing demand for Malay books as Malay schools and school libraries expanded throughout the Straits Settlements during the first 40 years of the twentieth century.